The Impact of Digital Orientation and Dynamic Capabilities on the Competitive Advantage of Small and Medium-sized Enterprises - Li, Lyusheng; Hye, A.K. Mahbubul; Shumnij, Sukumarn (Journal of Dhamma for Life, 2026)
This study the research aims to: (1) analyze the influence of digital orientation on competitive advantage, (2) evaluate its impact on the development of dynamic capabilities, and (3) explore the relationship between dynamic capabilities and competitive advantage. The study is grounded in the integration of digital orientation theory, dynamic capability theory, and competitive advantage frameworks to develop a comprehensive model explaining how SMEs can strengthen their market position in uncertain environments. A quantitative research design was employed, with data collected from 456 manufacturing SMEs using structured questionnaires as the primary research instrument. The data were analyzed using SPSS for descriptive statistics and preliminary analysis, and AMOS for structural equation modeling (SEM) to test the proposed hypotheses and examine the relationships among the constructs. The findings indicate that digital orientation has a significant positive effect on both dynamic capabilities and competitive advantage. Additionally, dynamic capabilities significantly enhance competitive advantage and serve as a mediator in the relationship between digital orientation and competitive advantage. The results further reveal that environmental uncertainty positively moderates the relationship between dynamic capabilities and competitive advantage, strengthening this relationship under higher levels of uncertainty. This study contributes to the literature by providing an integrated perspective on the mechanisms through which digital orientation drives SME competitive advantage. It also offers practical insights for SME managers on leveraging digital transformation and capability development to sustain competitiveness in dynamic and uncertain business environments.